2021
DOI: 10.3389/fphar.2020.588669
|View full text |Cite
|
Sign up to set email alerts
|

The G Protein Biased Small Molecule Apelin Agonist CMF-019 is Disease Modifying in Endothelial Cell Apoptosis In Vitro and Induces Vasodilatation Without Desensitisation In Vivo

Abstract: Signaling through the apelin receptor is beneficial for a number of diseases including pulmonary arterial hypertension. The endogenous small peptides, apelin and elabela/toddler, are downregulated in pulmonary arterial hypertension but are not suitable for exogenous administration owing to a lack of bioavailability, proteolytic instability and susceptibility to renal clearance. CMF-019, a small molecule apelin agonist that displays strong bias towards G protein signaling over β-arrestin (∼400 fold), may be mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…To further explore the role of the G-protein–independent signaling pathway in the response to apelin in CSE-treated coronary arteries, we compared the effects of apelin with CMF-019, a G-protein biased agonist at APJ receptors. 35 Our data show that, like apelin, CMF-019 causes endothelium-dependent relaxation of isolated rat coronary arteries and that this response is inhibited by the APJ receptor antagonist, F13A. In contrast to apelin, however, CMF-019–induced coronary artery relaxation was unaffected by exposure to CSE.…”
Section: Discussionmentioning
confidence: 53%
“…To further explore the role of the G-protein–independent signaling pathway in the response to apelin in CSE-treated coronary arteries, we compared the effects of apelin with CMF-019, a G-protein biased agonist at APJ receptors. 35 Our data show that, like apelin, CMF-019 causes endothelium-dependent relaxation of isolated rat coronary arteries and that this response is inhibited by the APJ receptor antagonist, F13A. In contrast to apelin, however, CMF-019–induced coronary artery relaxation was unaffected by exposure to CSE.…”
Section: Discussionmentioning
confidence: 53%
“…Stimulating the apelin pathway offers beneficial vasodilatory haemodynamic effects ( Maguire et al, 2009 ), increases cardiac contractility ( Perjes et al, 2014 ), has been shown to improve cardiac output in PAH patients ( Brash et al, 2018 ), and is suggested to address underlying drivers of PAH disease progression ( Falcao-Pires et al, 2009 ; Alastalo et al, 2011 ; Yang et al, 2017 ; 2019 ). However, a key limitation of apelin agonist therapy is β-arrestin dependent desensitisation of the target apelin receptor, necessitating the identification of G protein-biased ligands that offer better efficacy and cardioprotective effects ( Brame et al, 2015 ; Read et al, 2016 ; 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the aAPLNR + CMF-019 complex, no hydrogen bond between TM5 and TM7 transmembranal loops was expected, since CMF-019 is known to activate the G protein pathway selectively [ 47 , 53 ]. In addition, in the aAPLNR MD simulation, the hydrogen bonds between the two tyrosine residues of the TM5 and TM7 that are needed for the β-arrestin recruitment are formed [ 41 ], corroborating the idea that EC can recruit β-arrestin in the APLNR active state.…”
Section: Discussionmentioning
confidence: 99%